Analisis Desain Program Tahunan dan Program Semester dalam Kurikulum Lembaga Pendidikan - Yanah; Nur Eisyatur Rodliyah; Rucip; Ahmad Hamdan; Devy Habibi Muhammad (Al-Kindi, 2026)
Systematic learning planning is a key factor in achieving effective educational goals. This article comprehensively discusses the process of creating two essential planning documents: the Semester Program Design (Prosem) and the Annual Program Design (Prota). The main focus of this article is to provide practical guidance for educators in structuring these programs systematically, starting from the analysis of the academic calendar, time allocation, to the distribution of Basic Competencies (KD) and core subject matter. The methods used in writing this article include literature review and observation of field practices. The findings indicate that well-integrated Annual and Semester Program Designs can enhance learning effectiveness, facilitate the evaluation of learning outcomes, and ensure the smooth running of the teaching and learning process throughout the academic year. In conclusion, mastering the design of semester and annual programs is an essential competency for teachers to create directed and high-quality learning experiences.